The impact of unwashed aggregate on water quality emanating from permeable pavements - Biggs, Benjamin (Department of Civil Engineering, 2017)
Sustainable Drainage System (SuDS) technologies set out to mitigate the adverse effects of urban stormwater runoff, through a multi-objective approach. Permeable pavement systems (PPSs) are one of the most widely-adopted SuDS technologies in South Africa. South Africa is a water scarce country and the sustainable provision of water to its citizens is one of the most significant challenges facing the country. The demand on the potable water supply system could potentially be alleviated by substituting stormwater for potable water in a 'fit for purpose' manner. A Water Research Commission (WRC) pilot study is attempting to provide locally-relevant data on the treatment efficacy of PPS for possible use in stormwater collection, treatment and storage. A laboratory experiment comprising four separate units was set up to determine the capability of various different PPS designs to reduce selected pollutants from stormwater for South African conditions. Permeable concrete block pavers of the type commonly used in the City of Cape Town (CoCT) area were laid over four different layer-work options, one in each unit, using aggregate largely collected from stockpiles used to construct a nearby PPS in a parking area at the University of Cape Town. In the first phase of the experiment - the 'flushing phase' - clean tap water was applied to each unit over a period of time in quantities roughly representative of a typical rainy season in the CoCT and the discharge was collected and analysed. The measured parameters included: orthophosphate, ammonia, suspended solids, pH and conductivity. After the initial approach proved insufficient for flushing purposes, an accelerated flushing process was then implemented to prepare, as far as reasonably possible, the unwashed in-situ aggregate for the next phase of testing. The second phase examined the pollutant retention capacity of each PPS by comparing the concentrations of various pollutants before and after treatment. However, due to the unforeseen delayed release of the pollutants from the aggregate, the attempted flushing of the insitu stone again proved insufficient for flushing purposes. The pollutants continued leaching into the effluent showing an excess of the flushing volumes applied and thus the treatment efficacy results after the accelerated flushing were contaminated. Nonetheless, these findings provide useful insights for stormwater practitioners and indicated that failure to adhere to accepted international practice with respect to the washing of the aggregate prior to construction and the prevention of the ingress of dirt into the pavement layers during construction, have an adverse impact on the treatment performance of PPS. Therefore, the selection of base materials, in particular, the use of unwashed aggregate and the variation of the treatment layers and the layer material, affect the treatment performance of the permeable paving system and can pollute storm runoff passing through the PPS substantially for an extended period of time. Further research is needed to: determine suitable flushing methods when PPS are constructed with unwashed aggregate; and conduct additional laboratory testing using pre-washed stone to assess treatment efficacy of design variations. Thereafter, suitable fit-for-purpose applications for the treated effluent can be recommended. Keywords: Permeable pavement, stormwater harvesting, Sustainable Drainage System (SuDS), treatment efficacy, pollutant retention, fit for purpose, South Africa, unwashed aggregate.